Rhodopseudomonas acidophila, sp. n., a New Species of the Budding Purple Nonsulfur Bacteria - Pfennig, Norbert (1969)
A succinate-mineral salts medium of pH 5.2 provided selective enrichment conditions for Rhodomicrobium vannielii and for a new species belonging to the Athiorhodaceae, described herein as Rhodopseudomonas acidophila. Seven strains of the new species have been isolated from different sources in the United States and Germany. The cells are rod-shaped or ovoid, 1.0 to 1.3 μm wide and 2 to 5 μm long, and motile by means of polar flagella. Multiplication occurs by budding. The photopigments consist of bacteriochlorophyll a and carotenoids of the spirilloxanthin series, together with new carotenoids. All strains can grow either under anaerobic conditions in the light or under microaerophilic to aerobic conditions in the dark. No growth factors are required. The range of simple organic substrates photo-assimilated resembles that characteristic of Rhodomicrobium. Good photolithotrophic growth is possible at the expense of molecular hydrogen; thiosulfate and sulfide are not utilized.